ANALYSIS OF SELF-CONFIDENCE LEVELS AMONG ELEMENTARY SCHOOL CHILDREN IN BERAU REGENCY - Santi (Journal of Health, Sport, and Nursing, 2026)
Background: The elementary school years constitute a critical period for the development of competence, aligning with the psychosocial stage of "industry versus inferiority." Self-confidence serves as a protective factor against mental health disorders; however, data from Berau Regency indicates the presence of children falling into "borderline" and "abnormal" mental health categories. Methods: This study employed a descriptive quantitative design with a cross-sectional approach. The sample consisted of 105 fourth and fifth-grade students from SDN No. 002 Sambaliung, selected using consecutive sampling. The Lauster Self-Confidence Scale, comprising 19 items, was used as the research instrument. Data analysis was conducted using univariate analysis to determine frequency distributions and percentages. Results: The findings revealed that the majority of respondents (59 students or 56.2%) possessed a good level of self-confidence, while 46 students (43.8%) fell into the low category. The respondents were predominantly aged 10–11 years, and almost all (98.1%) lived with their biological parents. Conclusion and Recommendations: While most students demonstrated strong self-confidence, the prevalence of low self-confidence remained notably high. It is recommended that schools and community health centers (Puskesmas) conduct periodic screenings and develop psychosocial interventions based on expressive communication to strengthen the children's self-concept.